2017
DOI: 10.1016/j.syapm.2017.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the impact of rumen microbial communities on methane emissions and production traits in Holstein cows in a tropical climate

Abstract: The evaluation of how the gut microbiota affects both methane emissions and animal production is necessary in order to achieve methane mitigation without production losses. Toward this goal, the aim of this study was to correlate the rumen microbial communities (bacteria, archaea, and fungi) of high (HP), medium (MP), and low milk producing (LP), as well as dry (DC), Holstein dairy cows in an actual tropical production system with methane emissions and animal production traits. Overall, DC cows emitted more me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
37
3
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 36 publications
5
37
3
1
Order By: Relevance
“…At the genus or higher level, we found the unidentified genus of Neocallimastigaceae was the most predominant regardless of animal species, which is consistent with previous study on dairy cows [30]. Recent studies on dairy cows have found that Caecomyces was the second most dominant genus [11,45], while in the present study, Piromyces was the second prevalent genus in the rumen, irrespective of animal species, but the relative abundance of genus Caecomyces was very low (0.76%). Previous study has reported that the genus Piromyces can produce cellulolytic and hemicellulolytic enzymes [46,47], while members (Caecomyces communis) belonging to genus Caecomyces had glycoside and polysaccharide hydrolase activity.…”
Section: Discussionsupporting
confidence: 91%
“…At the genus or higher level, we found the unidentified genus of Neocallimastigaceae was the most predominant regardless of animal species, which is consistent with previous study on dairy cows [30]. Recent studies on dairy cows have found that Caecomyces was the second most dominant genus [11,45], while in the present study, Piromyces was the second prevalent genus in the rumen, irrespective of animal species, but the relative abundance of genus Caecomyces was very low (0.76%). Previous study has reported that the genus Piromyces can produce cellulolytic and hemicellulolytic enzymes [46,47], while members (Caecomyces communis) belonging to genus Caecomyces had glycoside and polysaccharide hydrolase activity.…”
Section: Discussionsupporting
confidence: 91%
“…The genus Schwartzia are asaccharolytic and can ferment succinic acid to produce propionic acid [60]. It was reported that bacteria a liated with Schwartzia were negatively correlated with CH 4 emissions [61], which was contrary to our results that monensin reduced the RA of Schwartzia and CH 4 emissions.…”
Section: Effects Of Alch Flah and Ant On Microbial Protein Synthesiscontrasting
confidence: 99%
“…The mulberry leaf avonoid showed the ability in methane inhibiting in sheep [35]. Schwartzia was found to be negatively correlated with methane emissions [36]. Thus, the detected increased abundance of Schwartzia in the MS group from the current study and its positively correlated with antioxidant function might be due to the roles of Schwartzia in competing with methanogenic bacteria.…”
Section: Discussionmentioning
confidence: 51%